2009
DOI: 10.1029/2008jg000857
|View full text |Cite
|
Sign up to set email alerts
|

Methane emission from Yangtze estuarine wetland, China

Abstract: [1] Yangtze estuary, lying in the subtropical monsoon region of China, is characterized by a unique environmental setting and endemic wetland plant species (Scirpus mariqueter). Methane (CH 4 ) emission fluxes were measured at the Yangtze estuarine wetland, Chongming Dongtan (CD), by a static closed chamber technique from May 2004 to April 2005. The results showed that CD is the source of atmospheric CH 4 , and emission fluxes had significant diurnal and seasonal variation. The annual average CH 4 emission flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 48 publications
1
38
1
Order By: Relevance
“…This suggests that the overall, soil carbon emissions would probably be overestimated if soil CO 2 and CH 4 effluxes are only measured during NTP in wetlands of the Yangtze River estuary, such as in Wang et al (2009).…”
Section: Tidal Effects On Co 2 and Ch 4 Emissionsmentioning
confidence: 95%
See 1 more Smart Citation
“…This suggests that the overall, soil carbon emissions would probably be overestimated if soil CO 2 and CH 4 effluxes are only measured during NTP in wetlands of the Yangtze River estuary, such as in Wang et al (2009).…”
Section: Tidal Effects On Co 2 and Ch 4 Emissionsmentioning
confidence: 95%
“…For instance, several laboratory incubation studies indicated that artificially simulated seawater addition increased soil CO 2 and CH 4 production compared with freshwater controls (Weston et al 2011), and induced a brief stimulation of soil CO 2 production but continuous suppression of CH 4 production, as compared with dilute seawater controls (Chambers et al 2011). However, in situ measurements of GHG effluxes in most studies were made while tidal flats were not inundated by tidewater, such as in Chen et al (2012), Livesley and Andrusiak (2012) and Wang et al (2009), probably because of operational difficulties during tidal inundations. Thus, estimated GHG emissions from coastal wetland soils have large uncertainties because of insufficient data reflecting tidal effects.…”
Section: Introductionmentioning
confidence: 91%
“…In three of the studies, both light and dark measurements were made, allowing a day length-integrated rate to be calculated for a 24-h period. We used the day length-integrated rate reported by Van der Nat and Middelburg (2000) in our analysis, and calculated such a rate from data reported by Hirota et al (2007) and Wang et al (2009) (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Yangtze and Min River Estuary, Taihu, Taiwan, and Hainan attracted much attention (Lu et al 1999;Chang and Yang 2003;Wang et al 2009a;Tong et al 2010). These studies showed that CH 4 emissions from herbaceous swamps were much higher than those from mangroves, and the emission rates from beaches were greatly influenced by tidal stages.…”
Section: Introductionmentioning
confidence: 99%